Pelaksanaan Pembelajaran Sosiologi Model CTL Berbasis Aplikasi Google Classroom di SMA Negeri 8 Pontianak - Citra Aprilina Kartika Arti; Imran; Iwan Ramadhan; Nuraini Asriati; Riama Al Hidayah (Jayapangus Press, 2022)
This study aims to determine how the planning, implementation and learning outcomes of the sociological model of CTL based on the Google Classroom Application. This research method used qualitative research method in the form of descriptive research. The results of the study indicated that what is used as a reference for learning planning is a online lesson plan which contains material on social problems that have been made in accordance with government regulations and preparations for using the Google Classroom Application. In the implementation of sociological learning using the CTL model based on the Google Classroom Application, the teacher did according to the lesson plans that have been made, namely from the introduction, core and closing activities. The learning process was implemented for three meetings to obtain learning outcomes. There are three domains of learning outcomes that become the teacher's reference, namely the realm of knowledge, the realm of attitudes & the realm of skills. The conclusion in the research on the implementation of the sociology CTL model based on the Google Classroom application in class XI IPS 1 SMA Negeri 8 Pontianak has been carried out in accordance with the learning implementation plan (RPP) by stating attitudes and skill assessments tested by the teacher to students to get good learning outcomes.